What evidence exists on the relationship between agricultural production and biodiversity in tropical rainforest areas? A systematic map protocol - Apriyani, V; Holle, MJM; Silangen, C; Oktalira, FT; Mumbunan, S (BioMed Central, 2021)
Background Agriculture produces food for billions of humans and creates livelihoods for farmers. However, the current food production systems, driven by the increasing food demand and the ever-growing human population, are undermining ecological resources, primarily those related to biodiversity. Accordingly, agricultural production in tropical rainforest countries has been a trade-off, as regions harbor high biodiversity while also being pressured by agricultural land expansion. Consequently, threats to biodiversity are inevitable and will likely affect the ecosystem service provisions necessary for the agricultural process. Presently, no study reviews and maps the evidence of relationships between biodiversity and agriculture in the tropical rainforest landscape. Therefore, such a study is necessary to identify the knowledge gaps and provide scientific evidence to the relevant policymakers for safeguarding biodiversity within agricultural policies. This study aims to collect available published literature that evaluates the relations of agricultural production and biodiversity. We will focus on the agriculture and priority crops in the countries producing the commodities situated in the tropical rainforest landscape.